Use of Water Hyacinth and Fermented Fruit Waste as BSF (Black Soldier Fly) Media on The Quality of BSF Maggot Flour - F. Ardiansyah; E. Susanto; Wahyuni (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
This study aims to assess BSF maggot flour’s quality using water hyacinth growing media and fermentedfruit waste using EM-4 and molasses. Held a total of 70 g of baby maggot was in the temple for 15 days.Eldest the feed used using fermented water hyacinth and fermented fruit waste with four treatmentsconsist of P0= 0% fermented water hyacinth+ 100% fermented fruit waste, P1= 25% fermented waterhyacinth+ 75% fermented fruit waste, P2= 50% fermented water hyacinth+ 50% fermented fruit waste,and 75% fermented water hyacinth+ 25% fermented fruit waste. The design of the experiment uses acompletely randomized design (CRD). The results showed that substitution of feeding 25% fermentedwater hyacinth+ 75% fermented fruit waste influenced the yield of BSF maggot flour (P <0.05), and therewas no effect on the pH quality of Maggot BSf flour (P> 0.05). The best results’ (substitution of feeding25% fermented water hyacinth+ 75% fermented fruit waste) has proximate content of dry matter89%, ash 11%, crude protein 35.5%, crude fat 12%, calcium 7%, nitrogen-free extract material 7%,metabolist energy 2939.64 kcal/ 100 g.